Grapevine varieties exhibiting differences in stomatal response to water deficit - Costa, Joaquim M. (2013)
Abstract. Knowledge on variety traits and physiological responses to stress is still scarce in Vitis vinifera L., limiting the optimisation of irrigation and breeding for high water use efficiency. We have characterised five grapevine varieties using thermal imaging, leaf gas exchange, leaf morphology and carbon isotope composition. Plants of the varieties Aragonez, Trincadeira, Cabernet Sauvignon, Syrah and Touriga Nacional were grown in field conditions. Two experiments were performed. In Experiment I (2006), vines of Aragonez and Trincadeira were either well irrigated (WI, 80% ETc), nonirrigated but rain fed (NI) or subjected to regulated deficit irrigation (RDI, 40% ETc) and studied along the summer season. In Experiment II (2006 and 2007), vines of the five varieties were subjected to RDI (30–40% ETc) and studied at veraison. In Experiment I, leaf temperature (Tleaf) correlated negatively with stomatal conductance (gs) and leaf water potential (Ypd). The inverse relationship between gs and Tleaf was highly significant in the afternoon. In Experiment II, the different genotypes showed different Tleaf for similar Ypd. Stomatal density did not correlate with gs suggesting that varieties have different stomatal control. Our results show that combined measurements of canopy temperature and Ypd can aid in better understanding of stomatal regulation in different grapevine varieties. Such variation in stomatal regulation should be taken into account in determining irrigation strategies